In the Intersection of Class and Indigeneity: The Political Economy of Indigenous People's Development in Kerala, India - Darley Jose Kjosavik (Ph D Thesis, 2005)
This thesis examines the development dilemmas of the indigenous people (adivasis) of Kerala, India. The goal in doing so is, first and foremost, to draw attention to the fact that the political economic processes that create wealth simultaneously produce poverty and deprivation. Drawing upon a wide range of theoretical and conceptual tools, this study addresses adivasi development in relation to the general development experience of Kerala, the new challenges posed by neoliberalism and decentralisation, the historical processes of the alienation of these communities from their resources and means of production, and the current struggles to reclaim rights to land. The analysis shows that the underdevelopment and marginalisation of adivasis is a product of the political economic processes in which they were forced to participate as unequal players, from a position of disadvantage. The nature of the conditions of their participation has been changing through history with the changing character of political economy at the local, national and global levels. Nevertheless, the adverse terms of the indigenous people's participation are still continuing and even being exacerbated by the new political economy of globalisation, as is evident from the intergenerational reproduction of underdevelopment and marginalisation. At the same time, their agency is gaining momentum through their continuing struggles for land. It is significant that in these land struggles they have not rejected the idea of development; instead, visions of modernity have been imagined into the struggle. This study shows that their struggle is directed towards emancipatory development, not towards reproducing `traditional' institutions. The study also recognises the limits to adivasi agency within the constraints of their structural location at the intersection of class and indigeneity. The adivasis of Kerala now seem to be trapped in a development triangle - the Kerala model of development, neoliberal policies and decentralisation. The dominant discourse on development in Kerala had been around the ideology of class. The Kerala model, which places heavy emphasis on distributional politics, emerged through this discourse. The study recognises the positive contributions of the class discourse to indigenous people's development. At the same time, the study also shows that knowledge produced from a proletarian standpoint epistemology would not be helpful in addressing the specific development questions of the indigenous people. Their material location at the classindigeneity intersection has to be given due recognition. The indigenist standpointepistemology developed in this study takes cognisance of the class-indigeneity intersectionality and will allow knowledge production in that direction. The challenge, then, for Kerala's Left movement is to articulate a new class politics sensitive to the intersectional nature of class and indigeneity. The study argues that such a class politics will be able to contribute to the emancipatory development of the indigenous people.